The effort of educators in improving the students' multi souls in SD IT Adzkia Padang - Rendy Nugraha Frasandy; Fauza Mashudi; Hasnah Baharuddin Syarif (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Abstract: This study aims to; first, to know the efforts made by SD IT Adzkia Padang educators in developing religious belief and knowledge in students. Second, to find out the efforts made by SD IT Adzkia Padang educators in developing students' religious attitudes and behavior. This research was packaged with a qualitative descriptive design, where the data sources were teachers, school principals, school administrators or committees, employees, and students at SD IT Adzkia Padang. In collecting data, the writer used observation, interview, and documentation techniques. To analyze the data, the writer used inductive, deductive and comparative methods.The results showed that; first, the efforts of educators in developing the religious spirit of students through the cultivation of religious beliefs in students, namely by providing understanding through the teaching and learning process, namely that in every lesson, both theme lessons and religious lessons and character are always associated with Islamic rule or known as integration. . Then carry out various religious activities such as prayer, memorizing the Koran and habituation. Second, in developing the attitude and behavior of the diversity of students, educators always provide guidance and supervision of the actions taken by students such as when taking ablution water, praying when starting a job, such as starting lessons, while eating, telling honestly and being gentle, 5S (smile, greetings, greetings, polite, polite), call ustadz / ustadzah to educators, ana for me, antum for you. Furthermore, always exercise control over the activities of students, so that students always maintain worship and have an inherent religious attitude and take place every day.Keywords: Teacher Effort, Diversity Spirit, Students